두 가지 연직혼합방안에 따른 해양대순환모형 혼합층깊이 및 상층수온 모사 민감도 비교 - 이동원; 장찬주; 예상욱; 박태욱; 신호정; 김동훈; 국종성; Yi, Dong-Won; Jang, Chan Joo; Yeh, Sang-Wook; Park, Taewook; Shin, Ho-Jeong; et al. (Ocean and polar research, 2013)
Vertical and horizontal mixing processes in the ocean mixed layer determine sea surface temperature and temperature variability. Accordingly, simulating these processes properly is crucial in order to obtain more accurate climate simulations and more reliable future projections using an ocean general circulation model (OGCM). In this study, by using Modular Ocean Model version 4 (MOM4) developed by Geophysical Fluid Dynamics Laboratory, the upper ocean temperature and mixed layer depth were simulated with two different vertical mixing schemes that are most widely used and then compared. The resultant differences were analyzed to understand the underlying mechanism, especially in the Tropical Pacific Ocean where the differences appeared to be the greatest. One of the schemes was the so-called KPP scheme that uses K-Profile parameterization with nonlocal vertical mixing and the other was the N scheme that was rather recently developed based on a second-order turbulence closure. In the equatorial Pacific, the N scheme simulates the mixed layer at a deeper level than the KPP scheme. One of the reasons is that the total vertical diffusivity coefficient simulated with the N scheme is ten times larger, at maximum, in the surface layer compared to the KPP scheme. Another reason is that the zonal current simulated with the N scheme peaks at a deeper ocean level than the KPP scheme, which indicates that the vertical shear was simulated on a larger scale by the N scheme and it enhanced the mixed layer depth. It is notable that while the N scheme simulates a deeper mixed layer in the equatorial Pacific compared to the KPP scheme, the sea surface temperature (SST) simulated with the N scheme was cooler in the central Pacific and warmer in the eastern Pacific. We postulated that the reason for this is that in the central Pacific atmospheric forcing plays an important role in determining SST and so does a strong upwelling in the eastern Pacific. In conclusion, what determines SST is crucial in interpreting the relationship between SST and mixed layer depth.